Comparison of the impact of exercise training combined with dietary intervention vs. dietary intervention alone in patients with obesity and metabolic syndrome—a systematic review - Cao, Youxiang; Xu, Rui; Zhang, Jie (Frontiers in Nutrition, 2025)
BackgroundMetabolic syndrome (MetS) is characterized by a cluster of metabolic risk factors, including abdominal obesity, raised triglycerides (TGs), lowered high-density lipoprotein cholesterol (HDL-c), hypertension, and impaired glucose tolerance. Multifaceted interventions, including dietary intervention (DI) and exercise training (Ex), are recommended for the treatment of MetS.ObjectiveOur study is a systematic review and meta-analysis comparing the efficacy of DI alone vs. DI with Ex (DI + Ex) on body composition, blood pressure (BP), and other cardiometabolic risk factors in patients with obesity and MetS.MethodWe searched PubMed, Web of Science, SPORTDiscus, and the Cochrane Library from their inception to 10 August 2025, for randomized controlled trials. We calculated mean differences (MD) or standardized mean differences (SMD) and 95% confidence intervals (CIs) using random- or fixed-effect models (depending on heterogeneity). The major outcome was improvement in MetS risk factors, including changes in waist circumference (WC), TGs, HDL-c, BP, and fasting plasma glucose (FPG). The secondary outcomes were body weight, body mass index (BMI), body fat (BF), fasting insulin, total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c), and glycated hemoglobin (HbA1c).ResultsIn this meta-analysis of 16 studies involving 902 individuals with obesity and MetS, the DI + Ex group demonstrated a significant advantage over DI for improving specific MetS risk factors. Specifically, the DI + Ex group showed superior efficacy in reducing WC [MD = 2.11 cm, 95% CI: (0.99, 3.23)] and FPG [SMD = 0.22, 95% CI: (0.03, 0.40)]. However, the addition of exercise did not confer a significant benefit for HDL-c, BP, or TG. Beyond the primary MetS factors, the combined intervention was also more effective for a range of secondary outcomes, including body weight, BMI, BF, TC, and LDL-c.ConclusionOur findings demonstrate that DI + Ex interventions yield significant improvements in multiple MetS risk factors among individuals with obesity. We recommend that healthcare providers and public health initiatives prioritize these integrated programs to optimize cardiometabolic health outcomes in this population.